2017
DOI: 10.1186/s40200-017-0302-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia in the world: a systematic review and meta- analysis of general population studies

Abstract: BackgroundSarcopenia, an age-related decline in muscle mass and function, is one of the most important health problems in elderly with a high rate of adverse outcomes. However, several studies have investigated the prevalence of sarcopenia in the world, the results have been inconsistent. The current systematic review and meta- analysis study was conducted to estimate the overall prevalence of sarcopenia in both genders in different regions of the world.MethodsElectronic databases, including MEDLINE (via PubMe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
555
7
53

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 780 publications
(643 citation statements)
references
References 58 publications
28
555
7
53
Order By: Relevance
“…To our knowledge, this is the first study to demonstrate the prognostic value of sarcopenia defined by muscle function and muscle mass in elderly patients Recent studies estimated the prevalence rates of sarcopenia to be approximately 1% -29% in people dwelling within the community [8-10], 10.2% -60% in hospitalized patients [11][12][13][14], and 14.3% -32.8% in those in long-term care [15,16]. A recent meta-analysis of studies in the general population, including 35 reports with a total of 58404 individuals, showed that the prevalence of sarcopenia defined by low muscle mass was 10% in both sexes [25], and the prevalence was higher for BIA-based methods than DXA-based methods (BIA: 13%, DXA: 8% in both sexes). Using the AWGS criteria, Han et al [26] reported that the prevalence rates of sarcopenia in 1069 older men and women in China were 6.4% and 11.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study to demonstrate the prognostic value of sarcopenia defined by muscle function and muscle mass in elderly patients Recent studies estimated the prevalence rates of sarcopenia to be approximately 1% -29% in people dwelling within the community [8-10], 10.2% -60% in hospitalized patients [11][12][13][14], and 14.3% -32.8% in those in long-term care [15,16]. A recent meta-analysis of studies in the general population, including 35 reports with a total of 58404 individuals, showed that the prevalence of sarcopenia defined by low muscle mass was 10% in both sexes [25], and the prevalence was higher for BIA-based methods than DXA-based methods (BIA: 13%, DXA: 8% in both sexes). Using the AWGS criteria, Han et al [26] reported that the prevalence rates of sarcopenia in 1069 older men and women in China were 6.4% and 11.5%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions can perpetuate the cycle of inactivity and muscle loss, eventually leading to frailty and even mortality [11][12][13][14]. While the prevalence of sarcopenia varies depending on how it is defined and the specific techniques used to measure muscle mass, it is estimated to occur in 25-45% of older adults in the U.S. and in a substantial proportion of older adults across the world even among healthy populations [7,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Muscle mass is lost at a rate of approximately 8% per decade between the ages 50 and 70 years; then weight loss is coupled with an accelerated loss of muscle mass, reaching a rate of 15% each decade [33]. The overall prevalence of sarcopenia is reported to be 10% [34]; with the continued increase in the older population, sarcopenia is becoming a serious global public health problem. Sarcopenia is associated with the ageing process [35]; loss of muscle mass and strength, which in turn affects balance, gait and overall ability to perform tasks of daily living, are hallmarks of this disease that is also a powerful predictor of disability [36].…”
Section: Sarcopeniamentioning
confidence: 99%